Isoflurane treatment for refractory and super-refractory status epilepticus in dogs - Sarpekidou, Eirini; Polyzois, Georgios; Papageorgiou, Virginia; Savvas, Ioannis; Polizopoulou, Zoe; Kazakos, George (Frontiers in Veterinary Science, 2024)
Introduction Resistant epileptic episodes, such as refractory status epilepticus (RSE) and super-refractory status epilepticus (SRSE), are neurological emergencies that require immediate medical treatment. Although inhalational anesthetics, such as isoflurane (ISO), have been proposed as a means of seizure control in dogs, there is currently a lack of both experimental and clinical studies on this subject. Study design This is a retrospective clinical study. Methods Records of dogs that received ISO for the management of RSE and SRSE during their intensive care unit (ICU) hospitalization at the Companion Animal Clinic of the Aristotle University of Thessaloniki were included in the present study. The study period spanned from February 2013 to March 2023. Dogs were identified as responders (R) when RSE/SRSE ceased after ISO administration, and the dogs were successfully discharged from the ICU after ISO discontinuation. Dogs were identified as non-responders (NR) when RSE/SRSE ceased after ISO administration, but RSE/SRSE reoccurred after ISO discontinuation. Additional data about the number and time of ISO cycles, the time of ICU hospitalization, the side effects of ISO administration, and an additional administration of antiepileptic drugs (AEDs) and anesthetic drugs were also recorded. Results A total of 20 dogs with 26 recorded RSE/SRSE episodes and 26 anesthetic cycles with ISO were included in the present study. The clinical termination of seizure activity was achieved 100% (26/26) in all episodes. In 73.1% (19/26) of the episodes, ISO administration resulted in successful RSE/SRSE treatment. Poor outcome was recorded in 26.9% (7/26) of the episodes because RSE/SRSE reoccurred after ISO discontinuation, and the dogs were euthanatized or died due to cardiac arrest. Inspiratory ISO ranged between 0.5 and 4.0%. The median time of the anesthetic cycles with ISO was 12.67 h (4.00–62.00). The median duration of the ICU hospitalization was 48.00 h (24.00–120.00). At least one ISO-related side effect was recorded in 23 out of 26 (88.5%) episodes. Conclusion To the authors’ knowledge, this is the first clinical study that addresses the administration of ISO for RSE/SRSE treatment in dogs. The use of ISO may be beneficial in terminating RSE/SRSE; however, further prospective studies are necessary to confirm this observation.